A review of impact testing on marine composite materials: Part II – Impact event and material parameters. (15th March 2018) - Sutherland, L.S.
Abstract: Composite materials are now used throughout the marine industry but their susceptibility to impact events is still an unresolved problem. The complex dependence of the impact behaviour and damage on the many material and impact event parameters discussed in part I means that impact testing must simulate the particular in-service case well. Hence, typical impact damage modes have been outlined for both monolithic and sandwich marine laminates, and the influence of impact indentor and target, and of material reinforcement, matrix, core and production process on impact behaviour are discussed. Together with parts I and III, this paper gives a comprehensive review of 'marine impact on marine composites', providing a valuable resource for the marine industry and research fields.